GUIDELINES FOR PRESIDENTING WOMEN FACING THE LAW IN DIVORCE WITH JUSTICE BASED IN KEBUMEN RELIGION COURT (IMPLEMENTATION OF PERMA NO. 3 YEAR 2017) - Trubus Wahyudi (Jurnal Pembaharuan Hukum, 2019)
An effort to improve the quality of justice with a gender perspective on July 11, 2017 the Supreme Court of the Republic of Indonesia has issued PERMA Number 3 of 2017 concerning Guidelines for Judging Women Against the Law. In line with this study, researchers assume specifically the implementation of Perma Number 3 of 2017 is related to women dealing with law in divorce cases related to the protection of women's rights (ex-wife) along with children's rights due to divorce based on justice. the implementation of PERMA No. 3 of 2017 in the field of litigation duties in the Religious Courts. In the end, judges in trying women's cases dealing with the law must reveal factors based on principles: Appreciation for human dignity, Non-discrimination, Gender Equality, Equality before the law, Justice, Utilization, for the sake of legal certainty.